Is High School Employment Consumption or Investment? - Ruhm, Christopher J. (Journal of Labor Economics, 1997)
This study examines how high school employment affects future economic attainment. There is no indication that light to moderate job commitments ever have a detrimental effect; instead, hours worked during the senior grade are positively correlated with future earnings, fringe benefits, and occupational status. These gains occur even though employed seniors attain slightly less education than their counterparts. The results are robust across a variety of specifications and suggest that student employment increases net investments in human capital particularly toward the end of high school and for females.